Universal valley control with polarization tailored light - Tyulnev, Igor; Jiménez-Galán, Álvaro; Poborska, Julita; Vamos, Lenard; Russell, Philip St. J.; Tani, Francesco; Smirnova, Olga; Ivanov, Misha; Silva, Rui F.; Biegert, Jens (Proceedings of SPIE - The International Society for Optical Engineering, 2024)
We demonstrate non-resonant optical control with bi-circular laser fields. Having the pump polarization simultaneously break time and space inversion symmetry allows for switching between K, K’ valleys of MoS2 even in its inversion symmetric bulk phase. This strong field effect enables a universal and material agnostic approach to valleytronics.
CRIS-Team Scopus Importer:2024-07-12
Keywords: haldane; hhg; mid-infrared; spectroscopy; transition-metal-dichalcogenide; trefoil; valley